Islamic Business Ethics as a Mediator between Service Quality, Loyalty, and Consumer Satisfaction: Evidence from Sharia Marketplaces in West Nusa Tenggara - Mariana Mariana; Ahmad Ridho Hidayat; Kukuh Tondoyekti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The growth of sharia-labeled marketplaces in Indonesia presents a critical paradox. While Muslim consumer demand for Islamic value-based platforms continues to rise, the widespread practice of sharia washing using Islamic labels purely as a marketing strategy without genuine implementation of Islamic business ethics has systematically eroded consumer trust. This study analyzes the effect of service quality and loyalty on consumer satisfaction through the mediation of Islamic business ethics (IEBI) among sharia marketplace consumers in West Nusa Tenggara (NTB). A quantitative approach employing Partial Least Squares- Structural Equation Modeling (PLS-SEM) was applied to 92 Muslim consumer respondents selected through purposive sampling. Results confirm all eight hypotheses. Service quality significantly affects Islamic business ethics (beta = 0.830), loyalty (beta = 0.759), and consumer satisfaction (beta = 0.831). Loyalty significantly affects Islamic business ethics (beta = 0.472) and consumer satisfaction (beta = 0.385). Islamic business ethics significantly affects consumer satisfaction (beta = 0.622). Most critically, Islamic business ethics partially mediates the effect of service quality on consumer satisfaction (VAF = 38.3%) and the effect of loyalty on consumer satisfaction (VAF = 43.3%). The negligible effect size of the loyalty-to-satisfaction direct path (f-square = 0.015) confirms that Muslim consumer loyalty only produces genuine satisfaction when mediated by a tangible perception of Islamic business ethics, not merely its label